THE INFLUENCE OF CALENDAR AND LEFLET MEDIA TOWARD THE TODDLER MOTHERS’ INCREASING OF KNOWLEDGE AND ATTITUDE TO POSYANDU - Bernadetha, Bernadetha; Kuswardinah, Asih; Raffy Rustiana, Eunike (Public Health Perspective Journal, 2020)
Posyandu is a health effort organized from, by, for and with the community, in order to empower the community and provide facilities to the community in obtaining basic health services, primarily to accelerate the reduction in maternal and under-five mortality rates. The purpose of this research was to analyze the influence of the calendar media on increasing the knowledge and attitudes of mothers of children under five (toddlers) in participating visits to Posyandu. This research was a quantitative research with two group pretest-posttest experimental methods. The calendar media was given to mothers of intervention group, and leaflet media to the control group. The study population was all mothers of toddlers in the Semarang City while the number of samples were 144 mothers who have toddlers aged 6-59 months in the Karangayu Health Center, Poncol Health Center and Bugangan Health Center. The sampling technique is purposive sampling. Data were analyzed using univariate and bivariate. The results showed that after the intervention increased knowledge of children under five in the calendar group (0.93%) was smaller than in the leaflet group (1.38%). The increase in the attitude of the toddlers in the calendar group (1.40%) was almost the same as the leaflet group (1.38%). Increasing the frequency of attendance of Toddler Children to the Posyandu in the calendar group (0.52%), is greater than in the leaflet group (0.29%). The conclusion of this study was that there was an increase in the frequency of attendance between the intervention groups using calendar media and the control groups using leaflet media. Interventions using calendar media increase the frequency of attendance more than using leaflet media.